Safety of contemporary menopausal hormonal therapy based on low doses of oestradiol and NETA - Stetkiewicz, Tomasz; Stachowiak, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2011)
Results of the large clinical trials Women’s Health Initiative (WHI), the Heart and Estrogen/progestin Replacement Study (HERS), and the Million Women Study (MWS) changed doctors’ and patients’ view of hormonal therapy and narrowed the indications for this treatment. Contemporary menopausal hormonal therapy, besides therapeutic safety, has to be highly individualized – adjusted to a particular patient’s needs, “tailor-made” for her (tailored therapy), and ensure understanding and compliance with the treatment regimen. The main advantage of low dose hormonal therapy is a similar therapeutic effect to therapy based on higher doses but with lower probability of adverse effects. To meet therapy safety and individualization requirements, one should remember about the correct choice of progestin, regarding possible adverse effects of this compound